2022
DOI: 10.1038/s41598-021-04207-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of mutational signature software on correlated signatures

Abstract: Mutational signatures are characteristic patterns of mutations generated by exogenous mutagens or by endogenous mutational processes. Mutational signatures are important for research into DNA damage and repair, aging, cancer biology, genetic toxicology, and epidemiology. Unsupervised learning can infer mutational signatures from the somatic mutations in large numbers of tumors, and separating correlated signatures is a notable challenge for this task. To investigate which methods can best meet this challenge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…First, it is worth mentioning that differences in occurrences of signatures in ERR vs. LRR can be affected by the sensitivity of the mutational signature’s extraction method, missing low magnitude exposure, and not solely due to regional differences 15 . However, we used one of the most accurate, robust and well-known frameworks 34 , and the results are consistent across cancer types and studies. Moreover, we performed the analyses using an additional mutational signatures algorithm, and found similar results (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 69%
“…First, it is worth mentioning that differences in occurrences of signatures in ERR vs. LRR can be affected by the sensitivity of the mutational signature’s extraction method, missing low magnitude exposure, and not solely due to regional differences 15 . However, we used one of the most accurate, robust and well-known frameworks 34 , and the results are consistent across cancer types and studies. Moreover, we performed the analyses using an additional mutational signatures algorithm, and found similar results (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 69%
“…As with any signature algorithm, the SigProfiler-based annotations 2 are not flawless. 30 , 31 We found that some of MESiCA’s “mistakes” were probably due to miss-annotation. For example, 31/33 (93.9%) of POLE samples which MESiCA “failed” to predict were probably falsely assigned to SBS10a-b, as their mutational load was not high as expected in POLE-mutated samples, their tumor types were not typical of POLE signatures, and no hotspot mutations in POLE were detected ( Figure S3 A).…”
Section: Resultsmentioning
confidence: 84%
“…While there has been some systematic benchmarking of mutational signature discovery methods on SBS data (Islam et al, 2020; Omichessan, Severi, & Perduca, 2019; Wu, Chua, Ng, Boot, & Rozen, 2022), we are unaware of previous benchmarking efforts on indel data. Based on analysis of reconstruction errors, we believe that the amount of resampling noise in the synthetic SBS and indel mutation data sets used here more closely resembles variability in real data than some previously used benchmarking data (Supplementary Figures S1,S2).…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the ability of mSigHdp with and without downsampling to discover mutational signatures in synthetic SBS and indel mutation data, and we compared this to the abilities of 4 other programs. While there has been some systematic benchmarking of mutational signature discovery methods on SBS data (1,6,(22)(23)(24) we are unaware of previous benchmarking efforts on indel data. Based on an analysis of the reconstruction of mutational spectra in real tumors using known signatures, we believe that the amount of resampling noise in the synthetic SBS and indel mutation data sets used here more closely resembles variability in real data than some previously used benchmarking data (Supplementary Figures S1, S2).…”
Section: Discussionmentioning
confidence: 99%